Eksistensi Interaksi Simbolik Kebudayaan Jual Beli Ternak Marosok di Payakumbuh Sumatra Barat - Putri, Aini Eka; Banowo, Emilianshah (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Globalization and technological advancements often change the patterns of symbolic interaction, especially in the culture of livestock trading through